Influence of TiC Particles on Mechanical and Tribological Characteristics of Advanced Aluminium Matrix Composites Fabricated through Ultrasonic-Assisted Stir Casting - Chitti Babu Golla; Mahammod Babar Pasha; Rajamalla Narasimha Rao; Syed Ismail; Manoj Gupta (Crystals, 2023)
The present investigation highlights the development of high-performance materials in the construction materials industry, with a special focus on the production of aluminium matrix composites (AMCs) containing titanium carbide (TiC) particles. The stir casting method with ultrasonic assistance was employed to enhance the mechanical and tribological properties. ASTM standards were employed to evaluate the influence of TiC particles on density, hardness (VHN), ultimate tensile strength (UTS), and wear resistance at various TiC weight fraction percentages (0.0 wt.%, 2.0 wt.%, 4.0 wt.%, 6.0 wt.%, and 8.0 wt.%). Field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) analysis were performed to analyse the microstructural changes and elemental phases present in the synthesised composite. Results revealed that the incorporation of 8 wt.% TiC reinforcement in the metal matrix composites demonstrated significant improvements compared to the base alloy. In particular, a substantial enhancement in hardness by 32%, a notable increase of 68% in UTS, and a significant 80% rise in yield strength were observed when contrasted with the pure aluminium alloy. The tensile fracture analysis of the specimens revealed the presence of dimples, voids, and cracks, suggesting a brittle nature. To assess the wear characteristics of the composites, dry sliding wear experiments were performed using a pin-on-disc wear tester. Incorporation of TiC particles resulted in a lower coefficient of friction than the base alloy, with the lowest friction coefficient being recorded at 0.266 for 6 wt.% TiC, according to the data. FESEM and energy-dispersive X-ray spectroscopy (EDXS) were used to examine the surfaces of the worn pin. Overall, the inclusion of TiC reinforcement particles in the matrix alloy greatly enhanced the wear resistance and friction coefficient of the Al-6TiC composites. Ploughing and adhesion under lower loads and delamination under higher loads were the wear mechanisms observed in the wear test.